Advance directives of will: nurses' perceptions of benefits and new demands - Saioron,Isabela (2017)
Abstract Objective: Knowing the perception of nurses about benefits and new demands brought by the Advance Directives (AD) in their daily work. Methods: Qualitative and exploratory research with data collected in 2016 through semi-structured interviews with 19 nurses from a Hospital in southern Brazil. Data analysis was given by the Discursive Textual Analysis. Results: Three categories emerged: The benefits of using ADs in nurses' daily routine; New demands for professionals related to the AD; The AD relevance for patients and their families. Conclusion: It is significant that legal, cultural and structural changes take place in order to take advantage of the ADs' benefits. It is essential to extend the access to ADs' information as part of care quality promotion regarding the terminal patients.